Quality of Life Studies in Skin Cancer Treatment and Reconstruction - Joseph, Andrew William (Facial Plastic Surgery, 2020)
Health-related quality of life (HRQOL) is an important measure of patient experience before, during, and after treatment for skin cancers. Over the past 20 years, a variety of generic as well as disease-specific HRQOL instruments have been developed to assess clinical outcomes. Clinical trials have increasingly focused on using HRQOL instruments as outcome measures. Patients with both cutaneous melanoma and nonmelanotic skin cancers have been found to experience improvement in HRQOL following surgical treatment and reconstruction. Individual demographic variables may further predict experience within each of these groups. Increasing use of HRQOL instruments in future studies comparing skin cancer treatments will allow physicians to better understand and optimize patient experiences.
Keywords: facial reconstruction; health-related quality of life; quality of life; facial plastic surgery; head and neck reconstruction; skin cancer